A targeted drug delivery system based on folic acid-functionalized upconversion luminescent nanoparticles. (April 2017) - Liang, Xuhua; Fan, Jun; Zhao, Yanyan; Cheng, Min; Wang, Xuejun; Jin, Ruyi; Sun, Tao
In this paper, multifunctional upconversion luminescent NaYF4 :Yb, Er nanoparticles with excellent hollow mesoporous structure were first fabricated. The effects of various reaction conditions on the morphology and size of the as-prepared samples were investigated in detail and Ostwald ripening effect was adapted to explain the formation mechanism of the HMUCNPs. Then, folic acid, a well-known ligand for the selective targeting of drugs into tumor cells, was conjugated to the surface of the hollow mesoporous structured upconversion luminescent nanoparticles (HMUCNPs) via amide reaction for targeted delivery of anticancer drugs so as to enhance the therapeutic efficacy. The properties were extensively studied, which indicated the obtained samples showed a typical hollow mesoporous structure and excellent upconversion luminescence that were useful for cell imaging and drug delivery. Drug storage/release properties were demonstrated to be pH responsive, in which the drug release might be beneficial at the reduced pH in certain cancerous tissues for targeted release and controlled therapy at the pathological sites. Meanwhile, DOX-NaYF4 :Yb, Er-FA HMUCNPs exhibited greater cytotoxicity than free doxorubicin hydrochloride because folic acid-conjugated HMUCNPs can be specifically taken up by FR-positive KB cells via a receptor-mediated endocytosis. Therefore, the folic acid-functionalized nanoparticles combining upconversion luminescent property and hollow mesoporous structure have potential for simultaneous targeted anticancer drug delivery and cell imaging.